2017
DOI: 10.1002/jctb.5191
|View full text |Cite
|
Sign up to set email alerts
|

Use of partially purified peroxidase of agricultural by‐product rice bran in deoxynivalenol reduction

Abstract: BACKGROUND Once peroxidase purification can improve substrate degradation capacity, peroxidase from rice bran was purified by expanded bed adsorption (EBA) coupled to diafiltration/ultrafiltration (DF/UF) and applied for deoxynivalenol (DON) reduction. RESULTS The DF/UF step was optimized according to membrane molecular weight cutoff (MWCO), DF cycles number, operation temperature and CaCl2 addition to the DF buffer. DON reduction tests were carried out with both clarified and purified peroxidase. The use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The reaction time for both systems, crude enzyme extract and purified, was 10 min. Gautério et al [35] also used the enzyme peroxidase purified from rice bran and found a DON degradation of 82% in the model system. The authors [35] emphasise that oxidative activity of the enzyme may not be the only mechanism to reduce the DON concentration and that proteins may exhibit adsorption capacity due to the active groups on the surface of the protein, which may occur in substitution or in conjunction with an oxidative mechanism.…”
Section: Reduction Of Ota Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction time for both systems, crude enzyme extract and purified, was 10 min. Gautério et al [35] also used the enzyme peroxidase purified from rice bran and found a DON degradation of 82% in the model system. The authors [35] emphasise that oxidative activity of the enzyme may not be the only mechanism to reduce the DON concentration and that proteins may exhibit adsorption capacity due to the active groups on the surface of the protein, which may occur in substitution or in conjunction with an oxidative mechanism.…”
Section: Reduction Of Ota Levelsmentioning
confidence: 99%
“…Gautério et al [35] reported a reduction of 81.7% DON in a model system, using PO also purified from rice bran. The authors emphasise that they cannot affirm whether there is an oxidative action of the enzyme in the trichothecene structure.…”
Section: Ota Concentration Reduction Mechanismmentioning
confidence: 99%
“…Another study was performed by Gautério et al, 45 where the peroxidase enzyme obtained and purified from rice bran was used in a model system resulting in a reduction of 81.7% of DON. The authors emphasize that they cannot affirm whether there is actually an oxidative action of the enzyme on the trichothecene structure.…”
Section: Trichothecene a And B Biodegradationmentioning
confidence: 99%
“…Among enzymes, commercial peroxidase (PO) has shown that it is effective at mitigating mycotoxins in different feed matrices [27,28]. Other studies have shown that PO obtained from plant extracts (e.g., soy and rice bran) is effective at mitigating mycotoxins [23,29,30], and depending on the materials to which it is applied, it may reach better results than commercial enzymes [24]. However, there is a lack of studies describing how application of PO to animal diets to inactivate fungal contaminants can interact with other nutrients and active compounds, affecting their potential bioavailability and influencing both the metabolism of the species and the quality of the final product [31].…”
Section: Introductionmentioning
confidence: 99%